The Emerging World of JAK Inhibitors - Uprety, Shraddha (Nepal Journal of Dermatology, Venereology & Leprology, 2024)
The Janus Kinase inhibitors are a new emerging class of small molecules. These target the Janus Kinase proteins located on the cell membrane. Janus Kinase proteins regulate the cellular transcription of several proteins and act as mediators in several cytokine pathways. Dysregulation in these cytokine pathways is responsible for disorders like alopecia areata, psoriasis, vitiligo, lichen planus, and more in dermatology. Contrary to the injectable biologics, these Janus kinase inhibitors can be taken per oral route and have greater patient acceptability. In this review, we seek to discuss the various indications of Janus Kinase inhibitors and their side effects. We also strive to discuss the monitoring for this class of drugs.